Pendampingan Menyusun Laporan Keuangan Pada UMKM Mefs Foods & Snacks - Septa Soraida; Nor Sahidah; Muslipah Muslipah; Muhammad Villah; Saidah Saidah; Emilia Rahman (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2024)
Micro, Small and Medium Enterprises (UMKM) MEFs Foods & Snacks is one of the MSMEs engaged in processing snacks which are packaged in such a way that they follow developments and people's tastes. In order to improve financial management at MEFs Foods & Snacks MSMEs, MEFs Foods & Snacks MSMEs are expected to be able to make financial reports so that MSME finances can become more accountable. The results achieved in this service are changes in the presentation of financial reports compared to the previous period, this is because MSME managers already understand how to record transactions, carry out records correctly so that the presentation of financial reports becomes more accurate and reflects the financial condition of MEFs Foods & Snacks MSMEs. Actually